Mechanisms behind protein-protein interactions in a β-lg-legumin co-precipitate. (30th March 2022) - Kristensen, H.T.; Christensen, M.; Hansen, M.S.; Hammershøj, M.; Dalsgaard, T.K.
Highlights: Protein-protein interactions of a β-lg-legumin co-precipitate and blend were studied. NEM, NaCl and SDS were used to target different interaction mechanisms. SDS showed no effect on protein-protein interactions. NEM and NaCl had significant effect, especially in combination. Interactions were dominated of disulphide bonds and electrostatic forces. Abstract: Interactions between pea protein and whey protein isolates in co-precipitates and blends consist of a combination of disulphide bonds, hydrophobic and electrostatic interactions. The present study aims to clarify if the two proteins with free thiols, β-lactoglobulin (β-lg) and legumin, played a significant role for these interactions. This study used different reagents to modify the conditions of interactions: N -ethylmaleimide (NEM) was used to block reactive thiols, while NaCl and SDS were used to prevent electrostatic or hydrophobic interactions, respectively. The effects of treatments were studied on protein solubility, structure and stability. SDS had no effect, while NEM and NaCl both had great effect, especially in combination. The results showed that interactions of β-lg and legumin in both co-precipitates and blends are a synergism of electrostatic interactions and disulphide bonds. Thus, β-lg and legumin are the main proteins responsible for previously observed interactions in protein isolates of whey and pea.